Healthand well-being in urban areas : the WHO Healthy Cities project - Santos, Luís N. V. (2012)
The increasing number of people in the city takes the countries and organizations to ask themselves about the direction of urban areas in the provision of quality life and sustainability.The WHO promotes the Healthy Cities project to encourage local planning actions to provide more health and sustainability for cities.Viana do Castelo follows this directivedeveloping a monitoring system that allows reflection on the promotion of the well-being and health care of itscitizens.